1998
DOI: 10.1042/bj3370045
|View full text |Cite
|
Sign up to set email alerts
|

Phenol sulphotransferase SULT1A1 polymorphism: molecular diagnosis and allele frequencies in Caucasian and African populations

Abstract: Sulphation, catalysed by members of the sulphotransferase (SULT) enzyme family, is an important component of the body's chemical defence mechanism, but also acts to bioactivate mutagens such as hydroxylated aryl and heterocyclic amines. A major human sulphotransferase, SULT1A1 (P-PST), metabolizes and/or bioactivates many drugs, iodothyronines and hydroxylated aromatic amines. The enzyme activity varies widely within the population and is under genetic control. We have developed an assay detecting a G-->A tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(14 citation statements)
references
References 29 publications
4
10
0
Order By: Relevance
“…Therefore the presence of normal cells and malignant cells without DNA lesions in the locus of CYP3A5 , CYP2D6 , SULT1A1 and UGT2B15 decreases the risk of genotype misclassification. This is also supported by the fact that allele frequencies of CYP3A5*3 , CYP2D6*1 , SULT1A1*2 and UGT2B15*2 in the current study population are comparable to those reported by others in Caucasian populations [18,19,26,27]. …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Therefore the presence of normal cells and malignant cells without DNA lesions in the locus of CYP3A5 , CYP2D6 , SULT1A1 and UGT2B15 decreases the risk of genotype misclassification. This is also supported by the fact that allele frequencies of CYP3A5*3 , CYP2D6*1 , SULT1A1*2 and UGT2B15*2 in the current study population are comparable to those reported by others in Caucasian populations [18,19,26,27]. …”
Section: Discussionsupporting
confidence: 91%
“…The primer sequences used in the PCR of CYP2D6 and SULT1A1 were adopted from Hanioka and colleagues [21] and Coughtrie and colleagues [26], respectively, whereas the CYP3A5 and UGT2B15 genes were amplified with forward (5'-ACCACCCAGCTTAACGAATG-3' and 5'-AGAGCTTGTTCAGAGGGGTCATGAG-3') and reverse (5'-AGCACAGGGAGTTGACCTTC-3' and 5'-AAATTCTCGATAGATGGATATATGG-3') primers, respectively. The following PCR reagents were added to a reaction volume of 20 μl: 2 mM MgCl 2 , 0.2 mM dNTPs, 0.5 unit of Taq DNA polymerase, and 1 μM each of forward and reverse primer in 1 × PCR buffer.…”
Section: Methodsmentioning
confidence: 99%
“…The CYP2D6 and SULT1A1 genes were amplified with PCR in separate reactions using 30 ng DNA and 60 ng DNA, respectively. The primer sequences used in the PCR of CYP2D6 and SULT1A1 were adopted from Hanioka and colleagues [14] and Coughtrie and colleagues [17]. The following PCR reagents were added to a reaction volume of 20 μl: 2 mM MgCl 2 , 0.2 mM dNTPs, 0.5 units Taq DNA polymerase, and 1 μM each of forward and reverse primer in 1 × PCR buffer.…”
Section: Methodsmentioning
confidence: 99%
“…SULT1A1 -specific primers and hybridization probes were used to detect G638A in exon 7. The primers for DNA amplification were previously described by Coughtrie and coworkers [21]. As sensor and anchor probes, we used LCRed640-CAgggAgCgCCCCACAA-p and gAACCATgAAgTCCACggTCTCCTCT-x, respectively.…”
Section: Methodsmentioning
confidence: 99%